EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DAN STUDENT TEAMS ACHIEVEMENT DIVISION BERBANTUAN MEDIA GEOGEBRA PADA MATERI PROGRAM LINEAR DITINJAU DARI KREATIVITAS BELAJAR SISWA KELAS XII IPA SMA NEGERI SE-KABUPATEN KUDUS - Ayuni, Puji; Mardiyana, Mardiyana; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
ABSTRACT: The objectives of this research were to investigate: (1) which learning model of the Geogebra-based TGT type, the Geogebra-based STAD type, and direct learning model results in a better learning achievement in the topic of Linear Program; (2) which students of those with the high learning creativity, those with the medium learning creativity, and those with the low learning creativity have a better learning achievement in the topic of Linear Program; (3) in each learning model, which students of those with the high learning creativity, those with the medium learning creativity, and those with the low learning creativity have a better learning achievement in the topic of Linear Program; (4) in each learning creativity, which learning model of the Geogebra-based TGT type, the Geogebra-based STAD type, and direct learning model results in a better learning achievement in the topic of discussion of Linear Program. This research used the quasi experimental research method with the factorial design of 3 x 3. The population of the research was all of the students in Grade XII of the Natural Science Program of Senior Secondary Schools of Kudus regency in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling. The samples consisted of three schools, namely: Senior Secondary School 1, Senior Secondary School 2, and Senior Secondary School 1 of Mejobo. The data of the research were analyzed by using the two-way analysis of variance (ANAVA) with unbalanced cells.The results of the analysis show that: (1) the Geogebra-based TGT type results in the same learning achievement in the topic of Linear Program as the Geogebra type-based STAD type, but the two former types result in a better learning achievement in the topic of Linear Program than the direct learning model; (2) the students with the high learning creativity have a better learning achievement in the topic of Linear Program than those with the medium learning creativity and those with the low learning creativity, and those with the medium learning creativity have a better learning achievement in the topic of Linear Program than those with the low learning creativity; (3) in the three learning models, the students with the high learning creativity have a better learning achievement in the topic of Linear Program than those with the medium learning creativity and those with the low learning creativity, and those with the medium learning creativity have a better learning achievement in the topic of discussion of Linear Program than those with the low learning creativity; and (4) the students with the high, medium and low learning creativity, Â the Geogebra-based TGT type results in the same learning achievement in the topic of Linear Program as the Geogebra type-based STAD type, but the two former types result in a better learning achievement in the topic of Linear Program than the direct learning modelKeywords: TGT, STAD and Geogebra